Biotechnological Advances in Amaranths Species and their Future Outlook in Crop Improvement - A Review - Pandey, R.M. (Recent Patents on DNA & Gene Sequences (Discontinued), 2013)
The grain amaranths were important food crops for the ancient middle and South American civilization. The germplasm of amaranths also has not been well characterized from the point of view of its exploitation for improvement of amaranths in general, a grain amaranth in particular. Among all under exploited crops grain amaranth is the most suitable candidate to begin with. As it is one of the most important under exploited crops being used as subsidiary or supplementary food. This work will report a study concerning the patent related to the biotechnological applications of Amaranths. It has been summarized in results that RAPD is a powerful approach to understand both inter-as-well as intra species relationships in the genus amaranths. One result indicates the presence of at least two repetitive families, such that at least one family of sequences is present in both cot1 as well as total nuclear DNA. The grain amaranth cultivation plays an important role in changing the economy of rural life. It is a source of dietary protein in strictly vegetarian people. In amaranths, somatic hybridization can be combined to the tertiary gene pools. Some of amaranth triploids are reported to be good in (Sharma SK, Dawson IK and Waugh R 1995) foliage and nutritional quality. They have broader leaves and good growth. Amaranth is grown under variety of soils and environmental conditions such as alkalinity, salinity, drought, frost etc. One of the ways to improve quality of grain amaranths to isolate variants of lysine genes products of which are enriched in essential amino acids. The high lysine content gene named as ‘amargene’ has been isolated and the patents have been used as biotechnological approach to introduce the gene in the tuber crop improvement The scope of biotechnology for the genetic improvement of grain amaranth crop has been described.
Keywords: Amaranthus